Comunicação quântica segura direta e polarização quântica usando estados contínuos da luz - Guerra, Antônio Geovan de Araújo Holanda (2017)
This thesis can be divided in three parts: I) Quantum secure direct communication protocols (QSDC). II) Homodyne single-photon detection. III) Quantum light polarization. Regarding the QSDC protocols, three new optical schemes were proposed. These new protocols use the spectral distribution of the light source and the frequency dependence of phase modulators in order to increase the security. In what concerns the single-photon detection, a homodyne single-photon detection experiment was realized. This experiment shows that an analog signal carried by a strongly attenuated coherent state can be recovered by an optical detector based on a PIN photodiode. At last, in the quantum polarization part, a new degree of polarisation measure based on the von Neumann entropy was proposed, as well the calculation of the quantum degree of polarization of continuum single-photon and coherent state was realized. Moreover, two experiments aiming to estimate the degree of polarisation by measuring the polarisation visibility were realized. Two situations were considered, the usage of a depolarizing channel and the semiconductor laser source working in different regimes of operation.